2022
DOI: 10.3389/fnins.2022.968839
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response relationship between the variables of unilateral optogenetic stimulation and transcallosal evoked responses in rat motor cortex

Abstract: Efficient interhemispheric integration of neural activity between left and right primary motor cortex (M1) is critical for inter-limb motor control. We employed optogenetic stimulation to establish a framework for probing transcallosal M1–M1 interactions in rats. We performed optogenetic stimulation of excitatory neurons in right M1 of male Sprague-Dawley rats. We recorded the transcallosal evoked potential in contralateral left M1 via chronically implanted electrodes. Recordings were performed under anesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 92 publications
(118 reference statements)
0
11
0
Order By: Relevance
“…The recorded LFP data was further filtered with a notch filter at 50 Hz and a 2 nd order Butterworth band-pass filter between 3 Hz and 300 Hz. For further details, see the previous study 45 .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The recorded LFP data was further filtered with a notch filter at 50 Hz and a 2 nd order Butterworth band-pass filter between 3 Hz and 300 Hz. For further details, see the previous study 45 .…”
Section: Methodsmentioning
confidence: 99%
“…All animal procedures were conducted in accordance with the ARRIVE guidelines, the European Communities Council Directive (2010/63/EU) and were approved by the Animal Experiments Inspectorate (2016-15-0201-00868) of Denmark. The electrophysiological raw data were collected as part of our previous study [36], where detailed methods can be found. The data was reanalyzed in the present study to obtain the TCT.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations